Management of Social Relations in the Development of Islamic Education in Integrated Islamic Junior High Schools in Jambi Province - M. Junaidi Habe (DINASTI RESEARCH, 2023)
The phenomenon of increasing existence of the Integrated Islamic Schools (IT) model in Indonesia, including in Jambi Province, has caught the attention of many researchers. The rapid development is, of course, based on various hypotheses, one of which is the management of social relations which are constructed in such a way as to support the existence of the IT school. This paper aims to highlight how Junior High School (SMP-IT) in the Province manages these social relations and uses them as an alternative in school development. This research uses a qualitative approach with data analysis techniques; reduction, display, and verification. The findings of this study indicate that social relations between SMP-IT schools and the community (pentahelix) are woven in such a solid way to benefit both parties; schools and communities, and of course this solidity is responsible for the existence and development of these IT institutions to date.